Project based learning on industrial informatics: applying IoT to urban garden - Hormigo-Aguilar, Javier; Rodríguez-Moreno, Andrés (My University, 2018)
The fast evolution of technologies forces teachers to trade content off for self-learning. PBL is one of the best ways to promote self-learning and simultaneously boost motivation. In this paper, we present our experience introducing project-based learning in the last year subject. New Internet of Things (IoT) topic allows us to carry out complete projects, integrating different technologies and tools. Moreover, the selection of open-source and standard free technologies makes easy and cheap the access to hardware and software platforms used. We carefully have picked communication, data management, and programming tools that we think would be attractive to our students. They can start making fast prototyping with little initial skills and, at the same time, these are serious and popular tools widely used in the industry. In this paper, we report on the design of a project-based learning for our course and the impact this has on the student satisfaction and motivation. Surveys taught us that tuning the courses towards developing real projects on the field, has a large impact on acceptance, learning objectives achievements and motivation towards the course content.
Keywords: Enseñanza - Innovaciones - Congresos; IoT; PBL; Teaching; Urban garden